A comparison of frequency and magnitude of head impacts between Pee Wee And Bantam youth ice hockey. Issue 6 (3rd June 2023) - Chen, Wesley; Post, Andrew; Karton, Clara; Gilchrist, Michael D.; Robidoux, Michael; Hoshizaki, T. Blaine
ABSTRACT: The purpose of this research was to compare the frequency and magnitude of head impact events between Pee Wee and Bantam ice hockey players. Videos of Pee Wee and Bantam boys' ice hockey were analysed to determine the frequency and type of head impact events. The head impact events were then reconstructed in the laboratory using physical and finite element models to determine the magnitude of strain in the brain tissues. The results showed that Pee Wee boys experienced more head impacts from elbows and boards, while Bantam players had more head impacts to the glass. Pee Wee and Bantam players experienced similar frequency and magnitudes of very low, low, and medium and above (med+) levels of strain to the brain. This research suggests to ice hockey leagues and coaches that to reduce the incidence of these levels of brain trauma, consideration must be given to either reducing the level of contact along the boards or the removal of body checking. In addition, companies who innovate in ice hockey should develop protective devices and equipment strategies that aim to reduce the risk of head injury from shoulder and glass impacts for Bantam players.